APPLICATION OF “MOODLE” E-LEARNING SYSTEM IN TEACHING LANGUAGE FOR SPECIFIC PURPOSES - Alexey N. Bekhterev; Anna V. Loginova (Открытое образование (Москва))
The article presents the development experience of online computer-assisted learning package based on modular object-oriented dynamic learning environment (MOODLE) that is designed to teach a foreign language for specific purposes in non-linguistic university. The developed package allows enhancing the teaching process by creating optimal conditions to realize the principles of teaching differentiation and individualization and also by stimulating the students’ motivation to learn the language through various methods and kinds of teaching tasks.